Common variable immunodeficiency leading to spinal subacute combined degeneration monitored by MRI. Issue 5 (1st May 1998) - Yousry, T A; Strupp, M; Brüning, R
Abstract : A patient is reported on with a common variable immunodeficiency syndrome (CVID), in whom chronic gastritis with antibodies against parietal cells and a cytomegalovirus associated enteritis led to vitamin B12 deficiency with consecutive subacute combined degeneration of the spinal cord. The resulting medullary changes, most probably representing demyelination, were visualised with MRI. The effects of treatment were also monitored over three years by MRI and clinical examination. The resolution of the MRI changes correlated with clinical improvement of the patient's signs. In the medical literature only five cases of vitamin B12 related spinal cord changes have been identified by MRI; none was caused by a CVID syndrome.